Harmoni Sosial Berbasis Kearifan Lokal “Doa Arwah” pada Masyarakat Perbatasan Indonesia-Timor Leste - Sri Suwartiningsih; Daru Purnomo (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
Indonesian citizens in the border of Indonesia and Timor Leste, particularly in Humusu-Wini village, NTT and the Sakato-Nepane district Oecusse, East Timor. Although these two areas are separated by different status of the country, the communities there always interact and visit each other. This research aims to explain local wisdom which motivates social harmony in the Indonesian border community of Timor Leste. To achieve these objectives, this study prioritizes methods such as participant-observation or direct participatory observation, interviews, literature review, and documents. The conclusions in Humusu Wini village, Insana Utara district, East Nusa Tenggara. From the results of the study, it was obtained that the local wisdom "Doa Arwah" as one of the ties of kinship between citizens who are now in different countries or across countries, so as to create social harmony